2022
DOI: 10.1088/1742-6596/2225/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide reinforced epoxy nanocomposites coatings for corrosion protection: a review

Abstract: Graphene oxide (GO) is a reinforcing filler material used in epoxy resin to make coatings for improving the corrosion resistance of epoxy. The synthesis methods of GO are discussed with their modification methods (covalently and non-covalently). The incorporation of GO in epoxy resin nanocomposites coatings shows the improved corrosion resistance and adhesion strength depends on the processing protocol and aspect ratio of GO. Modification of GO covalently and non-covalently and reinforced in epoxy nanocomposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…In view of the current circumstances, industrial protective coatings are one of the most efficient approaches for metal corrosion prevention. Either waterborne (WEP) or solvent-based epoxy (SEP) coatings are excessively used protective solutions in this domain due to their attractive mechanical, adhesion and chemical resistance properties (Chen et al , 2021a, 2021b; Golshekan and Shirini, 2019; Harsha et al , 2022; Njoku et al , 2017; Xue et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In view of the current circumstances, industrial protective coatings are one of the most efficient approaches for metal corrosion prevention. Either waterborne (WEP) or solvent-based epoxy (SEP) coatings are excessively used protective solutions in this domain due to their attractive mechanical, adhesion and chemical resistance properties (Chen et al , 2021a, 2021b; Golshekan and Shirini, 2019; Harsha et al , 2022; Njoku et al , 2017; Xue et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…According to another research on anti-corrosion coatings of epoxy/graphene oxide composites, Liu et al 29 reported that the addition of graphene oxide to the epoxy matrix effectively prevents liquids from penetrating into the epoxy/graphene oxide composite coatings as a result of increasing the density of the coating and also increasing the compaction of epoxy molecules. In review studies, Harsha et al 30 showed that, compared to pure epoxy matrix, graphene oxide in epoxy matrix causes highly corrosion-resistant coatings due to its high adhesion strength between graphene oxide and epoxy matrix. Also, according to the review studies of Hou et al, 31 graphene oxide provides better properties and performances than pristine graphene in epoxy composites and its use in anti-corrosion composite coatings, as well as more applications in the future.…”
Section: Introductionmentioning
confidence: 99%